Commercialization of bioinformatics and biotechnology products in Malaysia: an overview - San, Cheong Leng; Narayanasamy, Priyah; Ahmad Dahlan, Abdul Rahman (2012)
Commercialization of Research and Development (R&D) Products, particularly bioinformatics and biotechnology has always being overlooked by the industry and academic sectors. There are some misleading concepts that triggers both these sectors that commercialization of R&D products is not as part of their responsibilities. This is because the knowledge of R&D products emerges from academic world while commercialization involves business oriented field. This article is produced based on reference of various papers on commercialization of R&D products in Malaysia. Highlights of this article is to enlighten the current efforts and challenges faced by Malaysia in promoting R&D, specifically bioinformatics and biotechnology products, and produce thoughtful discussion in improving the current effort.